Differences in the diagnosis of primary cutaneous melanoma in the public and private healthcare systems in Joinville, Santa Catarina State, Brazil - Raquel Bissacotti Steglich; Silvana Cardoso; Maria Helena da Costa Naumann Gaertner; Karina Munhoz de Paula Alves Coelho; Tania Ferreira Cestari; Selma Cristina Franco (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Cutaneous melanoma accounts for up to 80% of deaths caused by skin cancer. Diagnostic suspicion and access to medical care and early intervention in suspected cases is vital to the patient's prognosis. Objectives: To compare demographic and histopathological characteristics of primary cutaneous melanoma diagnosed in the public healthcare system (Sistema Único de Saúde SUS) and the private system in Joinville, Santa Catarina State, Brazil. Methods: This cross-sectional retrospective study analyzed primary cutaneous melanoma cases recorded from 2003 to 2014 in the resident population of Joinville. Ethical approval was obtained from the local Research Ethics Committee. Results: 893 cases of primary cutaneous melanoma were identified. Patients in the private system were mostly younger, while there were more elderly patients in the public healthcare system (p <0.001). There was no statistically significant association between type of care (public/private) and gender or presence of multiple primary cutaneous melanomas. Histological diagnosis of superficial spreading melanoma was more common in patients treated in private healthcare, while nodular melanoma was more frequent in patients in the public healthcare system (p <0.001). Mean Breslow depth in patients treated in private healthcare was 1.35mm, compared to 2.72mm in the public system (p <0.001). Study limitations: This was a retrospective study using secondary databases. Conclusions: thin cutaneous melanoma (in situ cutaneous melanoma and Breslow T1) showed the strongest association with the private healthcare system, while thick cutaneous melanoma was more frequent in the public system (Breslow category T3 and T4) (p <0.001).